MRI Evaluation of the Normal and Abnormal Endolymphatic Duct in the Pediatric Population: A Comparison with High-Resolution CT - Clarke, R.L.; Isaacson, B.; Kutz, J.W.; Xi, Y.; Booth, T.N. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: An enlarged vestibular aqueduct is the most commonly reported imaging abnormality in children with sensorineural hearing loss. MR imaging is often used to evaluate pediatric sensorineural hearing loss; however, there are no well-established size criteria on MR imaging to diagnose an enlarged endolymphatic duct. The first purpose of the study was to determine a range of normal endolymphatic duct sizes on MR imaging and compare it with that in high-resolution CT. The second purpose was to assess the sensitivity and specificity of MR imaging in diagnosing an enlarged endolymphatic duct in patients with an enlarged vestibular aqueduct on CT.MATERIALS AND METHODS: Endolymphatic duct midaperture measurements were analyzed in 52 patients with no history of sensorineural hearing loss. Comparison of CT and MR imaging was made in a second cohort of 41 patients with a normal midaperture width on CT. The sensitivity and specificity of MR imaging were then evaluated in a third cohort of 24 patients with a documented enlarged vestibular aqueduct on CT.RESULTS: In 94 ears, normal endolymphatic duct midaperture measurements ranged from 0 to 0.9 mm on MR imaging. A significant correlation (P <.001) and moderate agreement were found between CT and MR imaging in 81 ears with a normal vestibular aqueduct on CT. Twenty-four patients had bilateral (n = 14) or unilateral (n = 10) enlarged vestibular aqueducts on CT, and the sensitivity and specificity of MR imaging were 97% and 100%, respectively, for a diagnosis of an enlarged endolymphatic duct.CONCLUSIONS: MR imaging measurements of the normal endolymphatic duct are similar to those established for CT. MR imaging is a useful tool for the diagnosis of enlarged vestibular aqueduct.CHARGEColoboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary abnormalities, and Ear abnormalities and deafnessELDendolymphatic ductEVAenlarged vestibular aqueductHRCThigh-resolution CTSNHLsensorineural hearing lossVAvestibular aqueduct